Evaluation of antimicrobial activity and activity on the autonomic nervous system of the lavender essential oils from Montenegro - Perovic, Svetlana; Pantovic, Snezana; Scepanovic, Valentina; Perovic, Andrej; Zivkovic, Vladimir; Zivkovic, Vladimir; Damjanovic Vratnica, Biljana (Progress in Nutrition, 2019)
This study investigates chemical composition and antimicrobial activity of essential oil of Lavandula officinalis from Montenegro, Mediterranean, and effects on autonomic nervous system. The oil was analysed by GC-MS technique in order to determine the majority compounds while dilution method was used to determine minimal inhibitory concentration. The present study assessed autonomic parameters such as blood pressure, heart rate, and skin temperature to determine the arousal level of the autonomic nervous system. In addition, subjects were asked to estimate their mood responses such as feeling pleasant or unpleasant, uncomfortable, sensuality, relaxation, or refreshing in order to assess subjective behavioural arousal. Chemical analysis by GC-MS identified 31 compounds in lavender oil representing 96.88% of the total oil. Linalool (24.84%), was a major component, together with linalyl acetate (22.39%), 1,8 cineole (18.13%) and camphor (12.88%). The investigated lavender oil consisted mostly of oxygenated monoterpenes (87.95%) and monoterpene hydrocarbons (7%). The lavender oil exhibited antimicrobial activity against Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Listeria monocytogenes (ATCC 19111), Proteus mirabilis (ATCC 25933) and Candida albicans (ATCC 10231) with an MIC of 1.4µl/ml. The results revealed that lavender oil caused significant decreases of blood pressure and heart rate, which indicated a decrease of autonomic arousal.